Pemberdayaan Masyarakat melalui Produksi Kopi, Pelatihan, dan Pendampingan Program CSR PT PLN Nusantara Power UP Paiton di Desa Batur Kabupaten Probolinggo - Danan Renafa (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
This community service activity was carried out to support capacity building for the Batur Village community in Gading District, Probolinggo Regency, by developing a coffee business, one of the village's superior potentials. This program is part of the Corporate Social Responsibility (CSR) of PT PLN (Persero) Nusantara Power UP Paiton, realized through training, mentoring, and strengthening community skills in coffee management. Various activities are carried out, including cultivation, post-harvest processing, and marketing of coffee products to achieve higher added value. The implementation of the activity actively involves coffee farmer groups and the local community. Through continuous training and mentoring, the community gains new knowledge and skills in better coffee processing techniques than the previously simple methods. These changes are evident in the community's increased ability to maintain product quality, manage the business, and understand the importance of group cooperation in supporting the development of the coffee business. In addition to providing benefits in technical skills, this activity also encourages community awareness of utilizing local potential to strengthen the village economy. The mentoring provided helps the community in dealing with various obstacles, especially those related to processing technology and product marketing. However, several challenges remain, including limited supporting facilities and the need for program sustainability to ensure that the benefits achieved continue to grow. Overall, this community service activity has made a positive contribution to increasing community capacity and supporting the creation of economic independence based on local potential in Batur Village.